The Determinants of Green Packaging that Influence Buyers' Willingness to Pay a Price Premium. Issue 3 (August 2018) - Singh, Gaganpreet; Pandey, Neeraj
The study examined the impact of green packaging on consumer behaviour. It was measured through willingness to pay since it acts as a proxy for actual behaviour. Using a sample of 343 respondents, the study empirically confirmed the effect of six factors grounded from "theory of consumption values" and "customer value creation framework" that offered uniqueness to green packaging and influenced buyers' willingness to pay a price premium.